Existential motives in Bergman’s films - Mróz, Jowita (Hybris, 2020)
Ingmar Bergman contributed his own specific aesthetics and language to the discussion on art. I will try to figure out if by means provided by cinematic techniques Bergman conducted his own reasoning on the matters of philosophical existentialism. In analyzing Prison, The Seventh Seal, Wild Strawberries, Winter Light and Cries and Whispers I am referring to director’s utterances, researcher’s interpretations and existential philosophy – Kierkegaard, Sartre, Heidegger and Jaspers. I take a look at his artistic output in a broad perspective. Based on the opinions expressed by Höök and Bergom-Larsson I assume that entire work of Bergman constitutes a coherent wholeness. Such perspective provides me with possibility to present the connection between Bergman’s movies and existential philosophy as well as his philosophical point of view.